STRATEGI PENGELOLAAN ZAKAT: ANALISIS KOMPARASI ERA KHALIFAH UMAR BIN ABDUL AZIZ DAN ERA SEKARANG DI INDONESIA - Mochammad Ridhwan Musthofa; Possumah, Bayu Taufiq (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2020)
Indonesia is a country with the largest number of Muslims in the world, this makes the potential of zakat in Indonesia reach 233.8 T. Caliph Umar bin Abdul Aziz is one of the successful caliphs in managing zakat. This study aims to determine the management strategy and distribution of zakat during the caliphate and in Indonesia, which then analyzed the possibility of its application in Indonesia. This analysis uses qualitative methods with literature review and content analysis analysis tools. The results of this study indicate that the fundamental factor of the success of the caliph in the management of zakat is in the legal system governed by the government. So that in the collection, management and distribution becomes centralized. In addition, public trust in the government also determines the success of the caliph in managing zakat.